Developing a Theory-Informed Smartphone App for Early Psychosis: Learning Points From a Multidisciplinary Collaboration - Berry, Natalie; Machin, Matthew; Ainsworth, John; Berry, Katherine; Edge, Dawn; Haddock, Gillian; Lewis, Shon; Morris, Rohan; Bucci, Sandra (Frontiers in Psychiatry, 2020)
Background Actissist is a smartphone app designed to deliver an intervention grounded in cognitive behaviour therapy for early psychosis. Actissist was developed by a multidisciplinary team of academics, clinicians, experts by experience and software engineers. Actissist has been tested in two trials, the first a proof-of-concept trial where Actissist was safe, acceptable and feasible, the second, a powered randomised controlled trial. Objective This article describes how our multidisciplinary team designed and developed Actissist. This article describes: i) how Actissist was informed by initial qualitative interviews and focus groups and an expert reference group; ii) refinements made to the app based on ongoing user feedback; iii) successes and challenges encountered; and iv) learning points and recommendations for involving stakeholders in digital health interventions. Methods Expert reference group meetings informed the development of Actissist and design of subsequent trials, which included individuals with lived experience of psychosis, clinicians, academics, computer scientists and software engineers. Person-centred stakeholder involvement was promoted using focus groups and qualitative interviews prior to the development of the app, which informed version one of Actissist. Interviews were carried out with participants who had used Actissist. Two further versions of Actissist were developed following additional rounds of testing. Results Multidisciplinary working throughout the Actissist project led to the development, inclusion and improvement of the app design and content. These changes and features included non-directive and compassionate content, co-designed recovery videos, relaxation exercises, goal-setting, psychoeducation material, ability to ‘favourite’ areas of the app that users found helpful, and goal-setting. Challenges to collaborative working included discrepancies between what stakeholders want and what it is technically possible to deliver, resource pressures, trying to deliver desired features within the boundaries of fundamental trial design considerations, and power imbalances associated with multidisciplinary working. Conclusions The involvement of stakeholders in the design and development and delivery of Actissist has been fundamental to our development approach. Through this collaborative process, we have identified different perspectives and ideas that would have not been generated by the research team alone. We hope that the successes and challenges highlighted are helpful for other researchers who wish to co-produce their work.